Are international differences in the outcomes of acute coronary syndromes apparent or real? A multilevel analysis. Issue 5 (14th April 2005) - Chang, Wei-Ching; Midodzi, William K; Westerhout, Cynthia M; Boersma, Eric; Cooper, Judith; Barnathan, Elliot S; Simoons, Maarten L; Wallentin, Lars; Ohman, E Magnus; Armstrong, Paul W
Abstract : Study objective: International variation in the outcomes of patients with acute coronary syndromes (ACS) has been well reported. The relative contributions of patient, hospital, and country level factors on clinical outcomes, however, remain unclear, and thus, was the objective of this study. Design: Multilevel logistic regression models were developed for death/(re)infarction (MI) at 30 days and death in one year, with patients (1st level) nested in hospitals (2nd level) and hospitals in countries (3rd level). Settings: The GUSTO IV ACS clinical trial was carried out at 458 hospital sites in 24 countries. Patients: 7800 non-ST segment elevation (NSTE) ACS patients. Main results: There were substantial variations among countries in the processes and outcomes of care at 30 days, ranging from 5.4% to 50.0% for percutaneous coronary intervention, 4.3% to 21.2% for coronary artery bypass graft surgery, 5.0% to 13.9% for 30 day death/(re)MI, and 4.9% to 14.8% for one year mortality. However, the residual inter-country variations in 30 day death/(re)MI and one year mortality became non-significant and nearly disappeared (p>0.500 for both) after adjusting for key baseline patient characteristics and hospital factors, which became significant (p<0.01 for both). Patient level factors accounted for 96%–99% of total variation in these end points, leaving the remaining 1% and 4% of variance attributable to hospital level factors. Conclusion: The international differences in clinical outcomes in this study of NSTE ACS are primarily accounted for by the patient level factors, with hospital level factors playing a minor part, and the country level factors a negligible one. These findings have significant policy and research implications involving international collaboration and comparisons.